APNOGRAPH – A PROMISING METHOD FOR DIAGNOSING SLEEP APNOEA. (June 2018) - Kiss, A.; Nagy, A.; Szakacs, Z.
Abstract : Objective: Sleep-related breath disorders are associated with impaired vitality and reduced life expectancy. In this respect particularly important role is played by obstructive sleep apnea syndrome (OSAS) causing higher cardiovascular morbid-mortality: hypertension, heart failure, increased risk of myocardial infarction and stroke. OSAS can result in early dementia, traffic and working injuries in connection with daytime falling asleep. Average prevalence is 2–4% (30% among hypertensive patients). Diagnostic gold standard is polysomnography (PSG) in special sleep-laboratories. Due to its complexity and price few laboratories are available in Hungary. Apnograph is a promising method of diagnosing OSAS. Device has 3 parts: ABPM, full-day 3-lead ECG-Holter (with HRV-analysis) and pulzoxymetry. Design and method: Authors made 41 measurements with card(X)plore Apnograph (Meditech Ltd. Hungary) in patients snoring during sleep. 32 male (M), 9 female (F) patients were investigated, mean age of 51, 1 (35–63) and 52, 2 (49–59) years respectively. Results: Beyond 4 known OSAS patients (2 M, 2F) 8 cases (5 M, 3F) were OSAS-negative (4 patients – 3 M, 1F –otorhinolaryngologic cause), slight abnormalities were revealed in 5 men (snoring diminished by theophyllin). In 4 patients (3 M, 1F) authors had no reliable data (atrial fibrillation and/or poor compliance). Significant abnormalities (repetitive desaturational epizodes, increased nighttime BP-variability, non-dipper pattern) confirmed suspicion of OSAS in 20 cases (17 M, 3F), for whom PSG were suggested in sleep-laboratory, all of them proved OSAS indicating CPAP or BiPAP therapy. Conclusions: Obstructive sleep apnea syndrome is an independent factor for cardiovascular morbid-mortality. Apnograph is a simply ambulanter method that can provide important paralel measured parameters which precise pre-diagnostic steps. By using this device active screening can be achieved and number of habitual snorers revealed. For really OSAS-suspected patients optimal time of PSG can be determined and urgent cases selected.